Black talc loaded manganese oxide antibacterial material and preparation method thereof
By synthesizing manganese oxide in situ on the surface of the black slippery stones, the antibacterial material of the black sliding stone load manganese oxide is formed, and the existing metal oxide antibacterial material has the accumulation phenomenon, complex synthetic process and biocompatibility in the actual application of the actual application. Sexual issues realize efficient antibacterial properties and good biocompatibility.
Patent Information
- Application Number
- CN202411438093.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-15
Smart Images

Figure CN119345227A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial materials, and in particular to an antibacterial material of black talc loaded with manganese oxide and a preparation method thereof. Background Art
[0002] Although metal oxide antibacterial materials exhibit good antibacterial properties, there are still many problems that need to be solved in practical applications. First, many metal oxides tend to aggregate in solution. This aggregation phenomenon not only reduces its effective surface area, but also may lead to a significant decrease in antibacterial activity. For example, zinc oxide nanoparticles tend to form aggregates in water, which limits the performance of their antibacterial properties. Secondly, the synthesis process of metal oxides is usually complicated and has strict requirements on operating conditions. This not only increases production costs, but also limits its promotion in large-scale applications. For example, although the commonly used sol-gel method can obtain materials with higher purity, due to its complex process, it often leads to insufficient uniformity of the material, thus affecting the antibacterial effect. Biocompatibility is also an important issue. Some metal oxides may induce toxic reactions in vivo, leading to cell damage or inflammatory reactions, limiting their application in biomedical materials.
[0003] At present, researchers have developed a variety of preparation technologies for metal oxide antibacterial materials, mainly including chemical precipitation, sol-gel, hydrothermal synthesis and solid-phase synthesis. These technologies have their own advantages and disadvantages. For example, chemical precipitation is widely used because of its simple operation and low cost, but it is easy to cause aggregation and inhomogeneity of materials; sol-gel method can achieve a relatively uniform particle distribution, but its process is complicated and it is highly sensitive to temperature and humidity, which often leads to insufficient uniformity of materials, thus affecting the antibacterial effect. The hydrothermal synthesis method can obtain high-purity and high-crystallinity metal oxides under high temperature and high pressure conditions, but the equipment investment is high and the applicability is limited. Although the solid-phase synthesis method can improve the stability of the material, it often takes a long time and high energy consumption. In order to solve these problems, researchers have also tried to combine metal oxides with other materials to form new composite materials. For example, metal oxides are combined with polymers, carbon materials, etc. to form composite materials, which can further improve the antibacterial performance and environmental adaptability. By adjusting the particle size, morphology and surface modification of metal oxides, their antibacterial effect can also be significantly improved. However, the preparation process of composite materials is often complicated, and the interaction at the material interface may lead to unstable performance.
[0004] In summary, although the existing metal oxide antibacterial material technology has made certain progress, it still has significant limitations. First, many metal oxides aggregate in practical applications, resulting in the inability to fully exert the antibacterial effect; second, the synthesis process is complicated and involves multiple steps, which increases production costs and time. At the same time, biocompatibility and safety issues have gradually received attention, and some metal oxides may have potential toxic effects on organisms. Therefore, it is particularly important to develop a new type of antibacterial material that can not only improve antibacterial properties but also have good biocompatibility. Summary of the invention
[0005] The purpose of the present invention is to provide a black talc-loaded manganese oxide antibacterial material and a preparation method thereof in view of the above-mentioned deficiencies in the prior art. The material not only has excellent antibacterial properties, but also improves biocompatibility, and is suitable for use in the fields of medical treatment and biomaterials.
[0006] The invention discloses an antibacterial material of black talc loaded with manganese oxide, comprising black talc and manganese oxide loaded on the surface of the black talc, wherein the manganese oxide comprises Mn3O4 and MnOOH.
[0007] The present invention discloses a method for preparing the above-mentioned black talc-loaded manganese oxide antibacterial material, which uses potassium permanganate, urea and cetyltrimethylammonium bromide as raw materials, adopts a hydrothermal reaction in-situ synthesis method, loads manganese oxide on the surface of black talc, and obtains the antibacterial material.
[0008] Furthermore, the temperature of the hydrothermal reaction is 150-190°C.
[0009] Further, the purity of the black talc is 70-85%.
[0010] Furthermore, black talc is dissolved in a certain amount of KMnO4 and urea solution, and then CTAB is added to the mixed solution and stirred in a water bath, and a hydrothermal reaction is carried out at 150-190°C. After the reaction is completed, it is filtered, dried and cooled to room temperature, and then taken out and fully ground to obtain a powder sample, namely the antibacterial material.
[0011] Furthermore, the mass ratio of black talc to KMnO4 is 0.4-0.8.
[0012] Further, the mixture was stirred in a water bath at 60-80°C for 30 min.
[0013] Further, drying at 60-80°C is performed and cooled to room temperature.
[0014] The present invention utilizes the unique layered structure of black talc and synthesizes manganese oxide on the surface of black talc by liquid phase in-situ synthesis method. The crystal phase and morphology of manganese oxide are controlled by adding black talc and regulating the synthesis temperature; high temperature and the addition of talc are conducive to the conversion of Mn3O4 to MnOOH; it can not only improve the stability of manganese oxide, reduce aggregation, and have high antibacterial properties, but also enhance its biocompatibility, and has the characteristics of low cytotoxicity, low hemolysis, etc., and is suitable for various biomedical occasions.
[0015] The preparation method of the invention is simple, easy to realize large-scale production, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 XRD patterns of samples prepared in Examples 1-3 and Comparative Examples 1-3;
[0017] Figure 2 XPS graphs of samples prepared in Examples 1-3 and Comparative Examples 1-3;
[0018] Figure 3 The SEM images of Examples 1-3 and Comparative Examples 1-3 are shown;
[0019] Figure 4 TEM of Examples 1-3 and Comparative Examples 1-3;
[0020] Figure 5-Figure 10 It is a statistical chart of the antibacterial performance test and biosafety test results of Comparative Examples 1-3 and Examples 1-3;
[0021] Fig.11 This is the SEM imaging of Example 3 (M / T-190) and bacteria. DETAILED DESCRIPTION
[0022] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0023] Example 1
[0024] In this example, M / T-150 was prepared. 0.79g KMnO4 and 0.075g urea were added to 20mL deionized water, followed by 0.225g CTAB dissolved, 0.5g black talc added, and heated in a 60°C water bath for 30min. After taking it out, it was transferred to a hydrothermal reactor and hydrothermally heated at 150°C. After the reaction was completed, it was filtered, dried at 60-80°C and cooled to room temperature, taken out and fully ground to obtain a powdered sample. M / T-150 was obtained.
[0025] Example 2
[0026] In this example, M / T-170 was prepared. 0.79g KMnO4 and 0.075g urea were added to 20mL deionized water, followed by 0.225g CTAB dissolved, 0.5g black talc added, and heated in a 60°C water bath for 30min. After taking it out, it was transferred to a hydrothermal reactor and hydrothermally heated at 170°C. After the reaction was completed, it was filtered, dried at 60-80°C and cooled to room temperature, taken out and fully ground to obtain a powdered sample. M / T-170 was obtained.
[0027] Example 3
[0028] In this example, M / T-190 was prepared. 0.79g KMnO4 and 0.075g urea were added to 20mL deionized water, followed by 0.225g CTAB dissolved, 0.5g black talc added, and heated in a 60°C water bath for 30min. After taking it out, it was transferred to a hydrothermal reactor and hydrothermally heated at 190°C. After the reaction was completed, it was filtered, dried at 60-80°C and cooled to room temperature, taken out and fully ground to obtain a powdered sample. M / T-190 was obtained.
[0029] Comparative Example 1
[0030] This comparative example prepares M-150. Take 0.79g KMnO4 and 0.075g urea, add them to 20mL deionized water, then add 0.225g CTAB to dissolve, put it into a 60℃ water bath and heat it for 30min, take it out and transfer it to a hydrothermal reactor, and perform hydrothermal treatment at 150℃. After the reaction is completed, filter it, dry it at 60-80℃ and cool it to room temperature, take it out and grind it thoroughly to obtain a powdered sample. M-150 is obtained.
[0031] Comparative Example 2
[0032] This comparative example prepares M-170. Take 0.79g KMnO4 and 0.075g urea, add them to 20mL deionized water, then add 0.225g CTAB to dissolve, put it into a 60℃ water bath and heat it for 30min, take it out and transfer it to a hydrothermal reactor, and perform hydrothermal at 170℃. After the reaction is completed, filter it, dry it at 60-80℃ and cool it to room temperature, take it out and grind it thoroughly to obtain a powdered sample. M-170 is obtained.
[0033] Comparative Example 3
[0034] This comparative example prepares M-190. Take 0.79g KMnO4 and 0.075g urea, add them to 20mL deionized water, then add 0.225g CTAB to dissolve, put it into a 60℃ water bath and heat it for 30min, take it out and transfer it to a hydrothermal reactor, and perform hydrothermal treatment at 190℃. After the reaction is completed, filter it, dry it at 60-80℃ and cool it to room temperature, take it out and grind it thoroughly to obtain a powdered sample. M-190 is obtained.
[0035] Antibacterial property test: Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) were grown in 5 ml of Luria-Bertani (LB) broth at 37°C for 4 hours. The bacterial culture was then diluted to 10 4 Up to 10 5 times to a concentration of about 10 6 CFU / mL. Different concentrations of antimicrobial materials (M-150, M-170, M-190, M / T-150, M / T-170, M / T-190) were added to the bacterial suspension and their antimicrobial effects were evaluated by plate count technique. The bacterial growth inhibition rate was determined by comparing the colony counts of the test samples and the control group.
[0036] Biosafety test: 1. Cytotoxicity: The cytotoxic effect of the composite material on BJ cells was determined by direct contact method. BJ cells were placed in 1640 medium rich in 10% fetal bovine serum and 1% penicillin / streptomycin, and cultured for three days in an environment of 5% CO2 at a temperature of 37°C. The samples were then placed in a 96-well plate and cultured for 24 hours. After the culture, 100 μL of CCK-8 (cell proliferation and toxicity detection kit) reagent was added to each well, and then cultured for another hour at 37°C. The absorbance at a wavelength of 450nm was measured using a plate reader to calculate the cell survival rate; 2. Hemolysis: Fresh rabbit blood treated with anticoagulants was rinsed with phosphate buffer to prepare a 5% red blood cell suspension. An equal amount of 500 μL of composite material solution was mixed with an equal amount of red blood cell suspension and cultured at 37°C for one hour. Phosphate buffer and water were used as negative and positive controls, respectively. After centrifugation, the supernatant was collected, and the absorbance was measured at a wavelength of 545nm using a microplate reader to calculate the hemolysis rate.
[0037] The results of antibacterial performance test and biosafety test are shown in Table 1 and Figure 5-Figure 10 shown.
[0038] Table 1. Biological properties of examples and comparative examples
[0039]
[0040] As can be seen from the above table, the antibacterial properties of the M / T-150 material prepared in Example 1 at a concentration of 0.50 mg / mL are 88.67% (E. coli) and 82.56% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL is 59.29%; and the hemolysis rate at a concentration of 0.10 mg / mL is 18.12%.
[0041] The antibacterial properties of the M / T-170 material prepared in Example 2 at a concentration of 0.50 mg / mL were 94.85% (E. coli) and 94.05% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 68.80%; and the hemolysis rate at a concentration of 0.10 mg / mL was 19.03%.
[0042] The antibacterial properties of the M / T-190 material prepared in Example 3 at a concentration of 0.50 mg / mL were 96.56% (E. coli) and 99.45% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 84.13%; and the hemolysis rate at a concentration of 0.10 mg / mL was 1.79%.
[0043] The antibacterial properties of the M-150 material prepared in Comparative Example 1 at a concentration of 0.50 mg / mL were 95.36% (E. coli) and 93.21% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 41.87%; and the hemolysis rate at a concentration of 0.10 mg / mL was 95.61%.
[0044] The antibacterial properties of the M-170 material prepared in Comparative Example 2 at a concentration of 0.50 mg / mL were 81.21% (E. coli) and 84.69% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 48.08%; and the hemolysis rate at a concentration of 0.10 mg / mL was 111.52%.
[0045] The antibacterial properties of the M-190 material prepared in Comparative Example 3 at a concentration of 0.50 mg / mL were 95.92% (E. coli) and 93.05% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 58.92%; and the hemolysis rate at a concentration of 0.10 mg / mL was 55.58%.
[0046] Figure 1 XRD of samples prepared in Examples 1-3 and Comparative Examples 1-3. The Mn oxides in the Examples and Comparative Examples are mixtures of Mn3O4 and MnOOH.
[0047] Figure 2XPS analysis of samples prepared in Examples 1-3 and Comparative Examples 1-3, the proportion of Mn valence states in the XPS analysis of the Examples and Comparative Examples, wherein the addition of black talc leads to an increase in the content of high-valence Mn (IV). At the same synthesis temperature, the addition of black talc increases the higher valence state, indicating that black talc has a regulating effect on the formation of MnOOH and Mn3O4, affecting the valence state distribution of Mn.
[0048] Figure 3 The SEM images of Examples 1-3 and Comparative Examples 1-3 show that MnOx alone has a rod-like morphology, and the higher the temperature, the larger the rods. The addition of black talc causes the rod-like MnOx to be converted into irregular nanoparticles. M / T-150 is a smaller nanowire, M / T-170 is a mixture of nanorods and nanoparticles, and M / T-190 is the most significant with most of the particles being irregular nanoparticles.
[0049] Figure 4 The TEM morphology and crystal phase analysis of Examples 1-3 and Comparative Examples 1-3. The main crystal phase observed for M-150 is Mn3O4, and the main crystal phase observed for M-170 and M-190 is Mn3O4. A mixed crystal phase of Mn3O4 and MnOOH is observed; the main crystal phase observed for M / T-150 and M / T-170 is Mn3O4, and the main crystal phase observed for M / T-190 is MnOOH. The addition of black talc will lead to the stability of the MnOOH crystal phase at 190 degrees Celsius.
[0050] Figure 5 The biological performance and antibacterial performance statistics of comparative example 1 are shown in FIG. 1 ; the biological performance of comparative example 1 (M-150) is high in antibacterial effect, with each concentration being higher than 95%; the cell survival rate is low, all lower than 75%, and the hemolysis rate is high, all higher than 5%.
[0051] Figure 6 It is a statistical chart of the biological performance and antibacterial performance of Comparative Example 2; the biological performance of Comparative Example 2 (M-170) has high antibacterial effect, with each concentration being higher than 95%; the cell survival rate is low, all lower than 75%, and the hemolysis rate is high, all higher than 5%.
[0052] Figure 7 It is a statistical chart of the biological properties and antibacterial properties of Comparative Example 3; the biological properties of Comparative Example 3 (M-190) have high antibacterial effects, all concentrations are higher than 95%; the cell survival rate is low, less than 75% when the concentration is higher than 0.025, and the hemolysis rate is high, higher than 5% when the concentration is higher than 0.10.
[0053] Figure 8The biological performance and antibacterial performance statistics of Example 1 are shown in the figure. The biological performance of Example 1 (M / T-150) shows that the antibacterial effect is average, which is higher than 95% when the concentration is lower than 0.5; the cell survival rate is average, which is lower than 75% when the concentration is higher than 0.025; the hemolysis rate is high, which is higher than 5% when the concentration is higher than 0.10.
[0054] Fig. 9 The biological performance and antibacterial performance statistics of Example 2 are shown in FIG. 1 . The biological performance of Example 2 (M / T-170) has a high antibacterial effect, which is higher than 95%; the cell survival rate is average, which is lower than 80% when the concentration is higher than 0.050; the hemolysis rate is high, which is higher than 5% when the concentration is higher than 0.10.
[0055] Fig.10 The biological performance and antibacterial performance statistics of Example 3 are as follows; the biological performance and antibacterial effect of Example 3 (M / T-190) are high, all higher than 95%; the cell survival rate is high, all higher than 75%, and the hemolysis rate is good, all higher than 5% when the concentration is higher than 0.20.
[0056] Fig.11 SEM imaging of Example 3 (M / T-190) and bacteria. The morphology of bacteria was deformed after the addition of M / T-190.
[0057] For matters not mentioned above, the prior art applies.
[0058] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. An antibacterial material of black talc loaded with manganese oxide, characterized in that: The invention comprises black talc and manganese oxide supported on the surface of the black talc, wherein the manganese oxide comprises Mn3O4 and MnOOH.
2. A method for preparing the antibacterial material of black talc loaded with manganese oxide as claimed in claim 1, characterized in that: Potassium permanganate, urea and hexadecyltrimethylammonium bromide are used as raw materials, and a hydrothermal reaction in-situ synthesis method is adopted to load manganese oxide on the surface of black talc to obtain the antibacterial material.
3. The preparation method according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 150-190°C.
4. The preparation method according to claim 2, characterized in that: The purity of black talc is 70-85%.
5. The preparation method according to claim 2, characterized in that: Black talc is dissolved in a certain amount of KMnO4 and urea solution, and then CTAB is added to the mixed solution and stirred in a water bath, and a hydrothermal reaction is carried out at 150-190°C. After the reaction is completed, it is filtered, dried and cooled to room temperature, and then taken out and fully ground to obtain a powder sample, i.e., the antibacterial material.
6. The preparation method according to claim 5, characterized in that: The mass ratio of black talc to KMnO4 is 0.4-0.
8.
7. The preparation method according to claim 5, characterized in that: Stir in a 60-80°C water bath for 30 min.
8. The preparation method according to claim 5, characterized in that: Dry at 60-80℃ and cool to room temperature.
Citation Information
Patent Citations
Black talc-based antibacterial agent as well as preparation method and application thereof
CN114158569A
Graphdiyne / manganous-manganic oxide nano composite material as well as preparation method and application thereof
CN117776267A
Nano-enzyme compound with core-shell structure as well as preparation method and application of nano-enzyme compound
CN118121718A
METHOD OF PRODUCING MANGANESE OXIDE Mn3O4 NANOPOWDER
RU2813907C1
Composite photocatalyst, manufacturing method thereof, kits containing composite photocatalyst, and bactericide photocatalyst
US20170144135A1